Acute Pancreatitis Task Force on Quality: Development of Quality Indicators for Acute Pancreatitis Management. (August 2019) - Vivian, Elaina; Cler, Leslie; Conwell, Darwin; Coté, Gregory A.; Dickerman, Richard; Freeman, Martin; Gardner, Timothy B.; Hawes, Robert H.; Kedia, Prashant; Krishnamoorthi, Rajesh; Oduor, Hellen; Pandol, Stephen J.; et al.
Abstract : INTRODUCTION: Detailed recommendations and guidelines for acute pancreatitis (AP) management currently exist. However, quality indicators (QIs) are required to measure performance in health care. The goal of the Acute Pancreatitis Task Force on Quality was to formally develop QIs for the management of patients with known or suspected AP using a modified version of the RAND/UCLA Appropriateness Methodology. METHODS: A multidisciplinary expert panel composed of physicians (gastroenterologists, hospitalists, and surgeons) who are acknowledged leaders in their specialties and who represent geographic and practice setting diversity was convened. A literature review was conducted, and a list of proposed QIs was developed. In 3 rounds, panelists reviewed literature, modified QIs, and rated them on the basis of scientific evidence, bias, interpretability, validity, necessity, and proposed performance targets. RESULTS: Supporting literature and a list of 71 proposed QIs across 10 AP domains (Diagnosis, Etiology, Initial Assessment and Risk Stratification, etc.) were sent to the expert panel to review and independently rate in round 1 (95% of panelists participated). Based on a round 2 face-to-face discussion of QIs (75% participation), 41 QIs were classified as valid. During round 3 (90% participation), panelists rated the 41 valid QIs for necessity and proposed performance thresholds. The final classification determined that 40 QIs were both valid and necessary. DISCUSSION: Hospitals and providers managing patients with known or suspected AP should ensure that patients receive high-quality care and desired outcomes according to current evidence-based best practices. This physician-led initiative formally developed 40 QIs and performance threshold targets for AP management. Validated QIs provide a dependable quantitative framework for health systems to monitor the quality of care provided to patients with known or suspected AP.